ANALISIS LIFE SKILL SISWA DENGAN PENDEKATAN CHEMOENTREPRENEURSHIP PADA MATERI ASAM BASA - Misdarianti Amelia; Arif Yasthophi (Journal of Chemistry Education and Integration, 2022)
This research aimed at knowing how student life skill after being taught by using Chemoentrepreneurship approach. This research was conducted at the second semester in the Academic Year of 2019/2020 in State Senior High School 1 East Kampar on Acid-Base lesson. It was a Descriptive research with The One-Shot Case Study design. The samples were the 31 of the eleventh-grade students of MIPA 1, and Purposive sampling technique was used in this research. The instruments of this research were observation, questionnaire, and test. The data analysis showed that student life skill on academic skill aspect was on very good category with the percentage 84.68% and vocational skill aspect was on good category with the percentage 79.82%. So, student life skill with Chemoentrepreneurship approach overall was on very good category with the percentage 82.25%.Keywords : Life Skill, Chemoentrepreneurship  Acid-Base